Implementasi Pemanfaatan Dinding Edukasi dalam Peningkatkan Literasi Numerasi Sebagai Perwujudan Karakter Kemadirian Siswa - Tri Handayani (Jurnal Didaktika Pendidikan Dasar, 2022)
This study aims to determine the increase in students' teaching and learning achievement in learning mathematics after the use of educational walls outside the school which was specially prepared for learning mathematics was activated. The paper is best practice report. Data obtained through questionnaires and interview guidelines. Data on the aspects of success were obtained from the responses of 30 students and 3 teachers in grades 4,5, and 6. The increase in student creativity was measured from the data on the success of student learning outcomes before and after the effort to use the outer walls of the school specifically about flat shapes and building spaces. The results, t was concluded that the the use of the outer wall of the school could increase the achievement of learning mathematics in flat-building materials and the habituation of numeracy literacy for both teachers and students at SD Negeri 7 Rejang Lebong. Educational walls that are created along the way students walk also make it easier for students to learn. Indirectly during breaks and sitting in the school environment, students are used to reading educational walls.